2020
DOI: 10.1186/s13046-020-01793-7
|View full text |Cite
|
Sign up to set email alerts
|

CircCDKN2B-AS1 interacts with IMP3 to stabilize hexokinase 2 mRNA and facilitate cervical squamous cell carcinoma aerobic glycolysis progression

Abstract: Background Circular RNAs (circRNAs) have been reported to play key roles in the development of various cancers. However, the biological functions and clinical significance of most circRNAs are still elusive. The purpose of this study was to explore the function and mechanism of a certain circRNA named circCDKN2B-AS1 in cervical cancer development and its potential value in the clinic. Methods qRT-PCR was used to verify the expression level of circC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 49 publications
0
37
0
Order By: Relevance
“…In our previous study, 18 circRNA sequencing profiling (GEO: GSE147009 ) was performed with a set of 12 cervical samples, including 6 normal cervical tissues and 6 cervical SCC tissues. The results of the sequencing yielded a total of 257 circRNAs that were significantly downregulated in cervical cancer tissues (the threshold values were |log 2 FC (fold change)| ≥ 2 and p < 0.05) ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, 18 circRNA sequencing profiling (GEO: GSE147009 ) was performed with a set of 12 cervical samples, including 6 normal cervical tissues and 6 cervical SCC tissues. The results of the sequencing yielded a total of 257 circRNAs that were significantly downregulated in cervical cancer tissues (the threshold values were |log 2 FC (fold change)| ≥ 2 and p < 0.05) ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…The northern blot assay was conducted as previously described. 18 The probe used in this study is listed in Table S6 .…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we had discovered some differentially expressed circRNAs in 6 human cervical cancer and 6 normal tissues through Ribo-zero RNA sequencing (available in GEO database: GSE147009) [ 26 ]. Among them, hsa_circ_0036730 (termed as circTICRR) was found to be up-regulated in cervical cancer tissues (fold change = 4.2, p < 0.05) and was validated to be a circRNA in circBase (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We found that triptolide downregulated the RNA-binding protein IMP3, which is required for ribosomal RNA processing and may predict prognosis in many cancers [ 49 51 ]. In breast cancer, IMP3 activates TAZ, a transcriptional co-activator of Hippo signaling that helps drive breast cancer stem cell function [ 49 ].…”
Section: Discussionmentioning
confidence: 99%